Haunted by Houses: Built and Lived Absences in a Transnational Mexican Community - Pauli, Julia (Anthropology of consciousness, 2026)
Globally, millions of migrants have sent money home to build a house. In early phases of migration, remittance houses are aspirational objects that materialize the continuous belonging of migrants to a community. In later stages, experiences of loss, estrangement, deportation, and death increasingly challenge these attachments. Drawing on my ethnographic research in a transnational community in rural Mexico since 1995, I explore how painful absences have shaped the building of and living in remittance houses. Disappeared and distant migrant kin haunt those living in remittance houses through their presence in material objects and social practices. I argue that attending to the different ways of being haunted by absences and loss in remittance houses can help bring forth nuances and complexities of how transnational communities respond to the inhumanity of migration between Mexico and the United States.